2018
DOI: 10.1080/09593985.2018.1460429
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity during hospitalization: Activities and preferences of adults versus older adults

Abstract: Both older adult and adult patients are physically inactive during hospitalization, and older adult patients express a greater need for additional information regarding physical activity after hospitalization than adult patients. Therefore, personalized strategies that inform and motivate patients to resume physical activities during hospitalization are needed regardless of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
0
22
1
2
Order By: Relevance
“…As argued in a recent editorial [9], hospital associated disabilities are still common despite three decades of study and knowledge about modifiable factors during hospitalization-e.g., limited mobility. Several studies have reported low levels of mobility in older patients hospitalized for medical illness (henceforth: older medical patients) [10][11][12][13][14]. Additionally, in a previous study, we found that older medical patients spent a median of 22 h a day lying or sitting and less than one hour a day standing and walking during hospitalization [15].…”
Section: Introductionmentioning
confidence: 49%
“…As argued in a recent editorial [9], hospital associated disabilities are still common despite three decades of study and knowledge about modifiable factors during hospitalization-e.g., limited mobility. Several studies have reported low levels of mobility in older patients hospitalized for medical illness (henceforth: older medical patients) [10][11][12][13][14]. Additionally, in a previous study, we found that older medical patients spent a median of 22 h a day lying or sitting and less than one hour a day standing and walking during hospitalization [15].…”
Section: Introductionmentioning
confidence: 49%
“…This important finding implies that older adults can be more physically active during hospitalization and underlines the need for in-hospital interventions to stimulate physical activity. 50,51 Our findings suggest that, of the of physical frailty factors described by Fried et al, 19 only age, 41 physical performance, and in-hospital step numbers are predictors of postdischarge step numbers. These findings support the theory that acute illness and age-related changes can lead to loss of muscle mass and physical performance, resulting in functional decline and reduced physical activity.…”
mentioning
confidence: 58%
“…This variety of modalities was based on the observation that preferences regarding the promotion of physical activity of patients who are hospitalized may vary considerably. 5 Nevertheless, there was a relatively high dropout rate from the study, and although this occurred in both phases and is thus not likely to be related to the intervention, it cannot be ruled out that the usage and satisfaction outcomes are biased.…”
Section: Discussionmentioning
confidence: 98%
“…In many patients, hospitalization is associated with physical inactivity and more time spent sedentary, in some leading to a longer length of stay and functional decline during and after hospitalization. 1 7 In the last 10 years, several randomized controlled trials (RCTs) studied the effect of physical activity interventions during and after hospitalization. A recent systematic review, concluding that the effect of physical activity interventions on physical performance in older patients during hospitalization was uncertain, included 15 trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation